Compreensão de estruturas sintáticas com movimento A’ e com movimento A em crianças portuguesas surdas com implante coclear.: Efeitos da idade de início de exposição ao input linguístico e do tempo de exposição à língua - Moita, Mara; Lobo, Maria (Revista da Associação Portuguesa de Linguística, 2022)
In the period in which language should be acquired, auditory input deprivation compromises oral language exposure. The literature reports difficulties in the oral comprehension of syntactic dependencies resulting from A’ movement, but no difficulties in the acquisition of syntactic structures with A-movement in hearing-impaired children with hearing aids. Our study investigates the effects of the total deprivation of linguistic input during the first year(s) of life (critical period of language acquisition) and length of language exposure on the comprehension of dependencies with A and A-bar movement (Wh- questions, relative clauses, and passives) in 47 Portuguese hearing-impaired children with cochlear implants. The results reveal that CI activation before age 3 combined with at least 6 years of language exposure determines comprehension of Wh- questions and relatives at the same level as the control group. The same does not happen with the comprehension of passives, that remain problematic in this population even after prolonged exposure. We discuss these findings in light of theoretical proposals that attribute the acquisition of passives to maturational constraints.